2022
DOI: 10.1021/acsomega.2c05873
|View full text |Cite
|
Sign up to set email alerts
|

Gemdimethyl Peptide Nucleic Acids (α/β/γ-gdm-PNA): E/Z-Rotamers Influence the Selectivity in the Formation of Parallel/Antiparallel gdm-PNA:DNA/RNA Duplexes

Abstract: Peptide nucleic acids (PNAs) consist of an aminoethylglycine (aeg) backbone to which the nucleobases are linked through a tertiary amide group and bind to complementary DNA/RNA in a sequence-specific manner. The flexible aeg backbone has been the target for several chemical modifications of the PNA to improve its properties such as specificity, solubility, etc. PNA monomers exhibit a mixture of two rotamers (Z/E) arising from the restricted rotation around the tertiary amide N−CO bond. We have recently demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Recently, Ganesh's group reported that the introduction of the gem-dimethyl (gdm) group influenced the Z/E rotamer ratio of the tertiary amide. The α-gdm monomer exclusively exhibits the Z-rotamer, whereas the β-gdm monomer exhibits the E-rotamer (Figure 9, 35) [91,92]. Those E/Z-rotamers influenced the orientation preference of PNA in the formation of the complex.…”
Section: Modification Of the Peptic Nucleic Acid Backbonementioning
confidence: 99%
“…Recently, Ganesh's group reported that the introduction of the gem-dimethyl (gdm) group influenced the Z/E rotamer ratio of the tertiary amide. The α-gdm monomer exclusively exhibits the Z-rotamer, whereas the β-gdm monomer exhibits the E-rotamer (Figure 9, 35) [91,92]. Those E/Z-rotamers influenced the orientation preference of PNA in the formation of the complex.…”
Section: Modification Of the Peptic Nucleic Acid Backbonementioning
confidence: 99%
“…PNAs have been reported to be stronger in binding to a complementary DNA or RNA strand due to a lack of electron repulsion from the neutral backbone. Moreover, PNAs are discriminatory in binding, allowing for high sequence specificity and affinity to a genetic target, and inherently capable of evading degradation by nucleases or proteases. , Unfortunately, the neutrality of the backbone of PNAs limits their incorporation into therapeutic design, as it has been reported that single-stranded PNAs suffer from aggregation in solution. , A way to prevent aggregation was to introduce chirality into the PNA backbone at positions α, β, or γ (Figure ). Modifications yielding αPNA and γPNA ,, are the most common, greatly reducing its limitations (poor membrane permeability, low aqueous solubility, and ambiguity in RNA binding orientation), , while also exploring a new frontier of preferential preorganization . The αPNA modifications have been assessed, discovering a loss of binding affinity toward the intended genetic target relative to nonmodified PNAs. On the other hand, γPNA modifications deliver improved binding affinity compared to nonmodified PNAs, ,, but the structure and dynamics of the promising miniature poly­(ethylene glycol) (miniPEG)-modified γPNAs have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 A way to prevent aggregation was to introduce chirality into the PNA backbone at positions α, β, or γ ( Figure 1 ). Modifications yielding αPNA 12 16 and γPNA 7 , 17 , 18 are the most common, greatly reducing its limitations (poor membrane permeability, low aqueous solubility, and ambiguity in RNA binding orientation), 7 , 9 while also exploring a new frontier of preferential preorganization. 9 The αPNA modifications have been assessed, discovering a loss of binding affinity toward the intended genetic target relative to nonmodified PNAs.…”
Section: Introductionmentioning
confidence: 99%
“…22 Identical terminal polarities in a double helical context are typically achieved through the formation of parallel stranded DNA by specific sequence choices, DNA analogs, pH control or by the incorporation of 3¢-3¢ and 5¢-5¢ linkages that leaves two 5¢ ends or 3¢ ends on the DNA motifs, respectively. [23][24][25][26] To introduce left-handed helices, Z-DNA forming sequences 27 or L-DNA 28 are typically incorporated into component DNA strands. Detailed study of underlying DNA structures and new DNA motifs informs the rational design of functional characteristics in self-assembled nanostructures.The motifs used in the field of DNA nanotechnology were initially inspired by structures that exist in nature.…”
mentioning
confidence: 99%
“…Chemical functionalization and design-based strategies yield nanostructures that are thermally stable 16 and nuclease-resistant. 17 Identical terminal polarities in a double helical context are typically achieved through specific sequence choices, DNA analogs or pH control to form parallel stranded DNA 18,19 and by the incorporation of 3′-3′ or 5′-5′ linkages that leaves two 5′ ends or 3′ ends on the DNA motifs respectively. 20 To introduce left-handed helices, Z-DNA forming sequences 21 or L-DNA component strands 22 are typically incorporated into component DNA strands.…”
mentioning
confidence: 99%